Determinants of Poverty in Indonesia and its Policy Implications, Multidimensional Approach to Measuring Poverty - Syahrul Fauzi, Ahmad; Runtiningsih, Sri; Hidayat, Faisal (Yayasan Lembaga Studi Makwa, 2022)
Poverty is not a single phenomenon, it is diverse and multidimensional. In Indonesia, which is socio-economically and demographically diverse, measurement of poverty based on an expenditure approach can’t comprehensively represent deprivation faced by the poor. This paper adopted Alkire and Foster’s multidimensional framework to estimate poverty and to identify the poor in Indonesia. It has analyzed data on 10 indicators pertaining to three valuable dimensions of well-being: education, health, and standard of living. This study uses data from Indonesia Family Life Survey (IFLS) 2014, then this study finds that 19.6% of the population in 2014 are categorized as being poor. In this study, poverty determinants are divided into three types including characteristics of regional, community and household. Based on results of logit estimation, all variables that representing regional characteristics industrial sector, agricultural sector and urban) has negative and significant effect on probability of a household to being poor. Then, there are two variables in community character that has negative and significant effect on probability of a household to being poor, that is access to electricity and access to school. Furthermore, there is one variable in household characteristics that has a negative and significant effect on probability of a household to being poor, that is home ownership.